Identification of reliable reference genes for gene expression studies of oil palm plantlets using normfinder and bestkeeper algorithms - A. H., Muhamad Afiq; Shaharuddin, Noor Azmi; R., Zubaidah (Malaysian Palm Oil Board, 2019)
Gene expression profiling analysis using real-time quantitative polymerase chain reaction (qRT-PCR) is commonly used due to its reliability and accuracy. Gene expression profiles of particular genes in different tissues and developmental stages aid in the understanding of their biological functions. However, the accuracy and reliability of qRT-PCR to study gene expression demand the use of species-specific reference genes for normalisation. Therefore, appropriate reference genes for qRT-PCR need to be determined for oil palm ( Elaeis guineensis) tissues. In this study, six candidate reference genes namely actin, Cyp2, GRAS, EgEfa1, F-box, and GLU were examined in leaf, node, internode, root, cabbage, shoot primordial and basal stem tissues of two-year old clonal oil palms. Two statistical algorithms, NormFinder and BestKeeper verified the stability of GRAS and Cyp2 reference genes in the oil palm tissues tested. The combination of Cyp2 and GRAS reference genes are recommended for gene expression normalisation profiles in nurserystage oil palm plantlets.